ANXIETY AND DEPRESSION IN MEDICAL STUDENTS OF A PRIVATE MEDICAL COLLEGE - Azad, Nadia; Shahid, Afshan; Abbas, Nadeem; Shaheen, Azra; Munir, Nargis (Journal of Ayub Medical College Abbottabad, 2017)
Background: Depression and anxiety are the common mental disorders with a prevalence of 10-44% in developing countries and is the fourth leading cause of morbidity. Undergraduate medical studies are generally perceived to be more stressful for the students as compared to other undergraduate programs as students have to undergo strenuous curriculum and evaluation which may lead to many emotional stresses that may end with psychiatric disorders like depression and anxiety. This study aimed to determine the frequency of anxiety and depression in medical students of Foundation University Medical College (FUMC), Rawalpindi. Methods: In this cross-sectional study, Beck Depressive Inventory and Beck Anxiety scales were used to assess anxiety and depression at three different times of the Academic year. All five-year students were included in the study. Results: Out of a sample of 150 students, mild depression was seen in 37.46% and moderate to severe depression was observed in 14% students. About 19% of the students had moderate to severe anxiety. In Second year students time of assessment was significantly related to depression and anxiety (p-0.000). Females had higher association with depression in final year (p-0.037). Conclusion: High psychiatric morbidity found needs to be identified and treated at the earliest; otherwise it can lead to serious consequences such as suicidal ideation and burnout. Keywords: Anxiety, depression, medical students